Overview of modelling techniques for greenhouse microclimate environment and evapotranspiration - Yan, Haofang; Acquah, Samuel Joe; Zhang, Jianyun; Wang, Guoqing; Zhang, Chuan; Darko, Ransford Opoku (International Journal of Agricultural and Biological Engineering, 2021)
Domestication of plants by man through greenhouse crop production has revolutionized agricultural farming systems worldwide. Selecting the appropriate greenhouse technology together with the user-friendly evapotranspiration (ETc) model can optimize crop water use. The greenhouse microclimate environment has nearly zero wind speed and low radiation, hence low transpiration due to high temperature and humidity. Therefore, matching the greenhouse microclimate with the appropriate ETc model will certainly optimize crop water use efficiency since water is becoming a scarce resource globally, more so in the greenhouse environment. This is one of the main reasons why the gap between the dissemination of various advanced ETc models and the application by the greenhouse crop producers’ community needs to be bridged. The likelihood or chances of rapidly disseminating and adopting advances in ETc estimating technology by a larger greenhouse crop producers community will increase if greenhouse ETc models become more user-friendly and available. The contribution of the greenhouse system to increased and sustainable food production must come through improved disseminating, adopting and use of existing greenhouse ETc models. FAO recommends a standard approach for the determination of crop water requirements utilizing the product of reference evapotranspiration (ET0) and crop coefficient (Kc) values. The FAO approach can also be used in greenhouse cultivation systems. However, studies connecting greenhouse technologies and methodologies for measuring ET0 or ETc in greenhouses are not available. There are also few studies undertaken that compared the performance of ET0 or ETc models under different categories of greenhouse conditions. In this review, a link between greenhouse technology and ET0 model or ETc model, and how existing knowledge and methodologies in ET0 or ETc measurements can actually enhance the sustainability of greenhouse farming have been highlighted. The categories of greenhouses, equipment commonly used, and the data collected for ET0 and ETc measurements have been established in the article. This review aimed to evaluate and summarize ET0 and ETc models currently available and being used in the various greenhouse categories. The accuracy assessment levels of the ET0 models about the category of the greenhouse microclimate environment were carried out. Keywords: greenhouse microclimate environment, reference evapotranspiration models, crop evapotranspiration, overviewDOI: 10.25165/j.ijabe.20211406.3948Citation: Yan H F, Acquah S J, Zhang J Y, Wang G Q, Zhang C, Darko R O. Overview of modelling techniques for greenhouse microclimate environment and evapotranspiration. Int J Agric & Biol Eng, 2021; 14(6): 1–8.